ANALYSIS OF PREGNANCY IN WOMEN WITH PNEUMONIA - Nadirkhanova, N.S.; Asatova, M.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Analysis of the pneumonia cases in pregnant women. Materials and methods: We conducted out a prospective study of pneumonia during pregnancy cases in women attending to the hospital. The study was conducted in the City Perinatal Center No. 1 of Tashkent and the Regional Perinatal Center in Bukhara city from 2009 to 2017. The sample includes 180 pregnant women. Results: 47.2% of pregnant women had severe community-acquired pneumonia. 14.4% of pregnant women with normal body temperature and without wheezing had pneumonia, the diagnosis of which was made on the basis of signs of intoxication, the presence of weakened breathing and radiological criteria - the presence of inflammation. Conclusions: With progression of severity of pneumonia decreased hematocrit, urine volume and total protein, increased leukocytosis and the process of intravascular thrombosis.